Integrated management of living mulches for weed control: A review - Bhaskar, Vinay; Westbrook, Anna S; Bellinder, Robin R; DiTommaso, Antonio (Weed technology, 2021)
Living mulches are cover crops grown simultaneously with and in close proximity to cash crops. Advantages of living mulches over dead cover crops may include increased weed suppression, reduced erosion and leaching, better soil health, and greater resource-use efficiency. Advantages of living mulches over synthetic mulches may include enhanced agroecosystem biodiversity and suitability for a wider range of cropping systems. A major disadvantage of this practice is the potential for competition between living mulches and cash crops. The intensity and outcome of mulch-crop competition depend on agroecosystem management as well as climate and other factors. In this review, we consider the management of living mulches for weed control in field and vegetable cropping systems of temperate environments. More than 50 yr of research have demonstrated that mechanical or chemical suppression of a living mulch can limit mulch-crop competition without killing the mulch and thereby losing its benefits. Such tactics can also contribute to weed suppression. Mechanical and chemical regulation should be combined with cultural practices that give the main crop a competitive advantage over the living mulch, which, in turn, outcompetes the weeds. Promising approaches include crop and mulch cultivar selection; changes to planting time, density, and planting pattern; and changes to fertilization or irrigation regimes. A systems approach to living mulch management, including an increased emphasis on the interactions between management methods, may increase the benefits and lower the risks associated with this practice.